Early antenatal care visit as indicator for health equity monitoring - Razum, Oliver; Bozorgmehr, Kayvan (The lancet. Global health, 2018)
Early antenatal care visits can be used as an indicator for health equity monitoring - in the context of the Sustainable Development Goals (SDGs). National-level surveys, - health information system data, and perinatal studies demonstrate substantial differences - between countries grouped by income in the proportion of women initiating the first - antenatal care visit in the first trimester of pregnancy. In the analysis by Ann-Beth - Moller and colleagues (October, 2017),1 early antenatal care coverage showed an inverse - association with country-level income, ranging from more than 80% in high-income countries - to 52% in lower-middle-income and 24% in low-income countries in 2013.